2020
DOI: 10.1128/jvi.01531-19
|View full text |Cite
|
Sign up to set email alerts
|

PACSIN2 Interacts with Nonstructural Protein 5A and Regulates Hepatitis C Virus Assembly

Abstract: Hepatitis C virus (HCV) is a major etiologic agent of chronic liver diseases. HCV is highly dependent on cellular machinery for viral propagation. Using protein microarray analysis, we previously identified 90 cellular proteins as nonstructural 5A (NS5A) interacting partners. Of these, protein kinase C and casein kinase substrate in neurons protein 2 (PACSIN2) was selected for further study. PACSIN2 belongs to the PACSIN family, which is involved in the formation of caveolae. Protein interaction between NS5A a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
(93 reference statements)
0
17
0
Order By: Relevance
“…Perilipin-2 expression is required for trafficking of core and NS5A to LDs and for the formation of HCV particles (15). We also showed that overexpression of PACSIN2 promotes NS5A and core interaction, which facilitates HCV particle assembly (16).…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…Perilipin-2 expression is required for trafficking of core and NS5A to LDs and for the formation of HCV particles (15). We also showed that overexpression of PACSIN2 promotes NS5A and core interaction, which facilitates HCV particle assembly (16).…”
mentioning
confidence: 67%
“…However, the proportion of intracellular and extracellular infectivity was not altered in cortactin knockdown cells (Fig. 5E), indicating that cortactin might be involved in the assembly step but not the release step of the HCV life cycle (16,(42)(43)(44).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Nguyen et al sought to investigate the role of protein kinase C and casein kinase substrate in neurons protein 2 (PACSIN2) interactions with HCV NS5A protein. Their data indicate that HCV exploits the pro-viral cellular function of PACSIN2 to promote viral assembly [11]. Takeo et al examined the potency of HCV NS3-specific nanobodies in HCV-infected cells and found that HCV NS3-specific nanobodies do not affect HCV RNA replication, but potently inhibit virus assembly at the stage of nucleocapsid envelopment.…”
Section: Viral Assembly and Virus-host Interactionmentioning
confidence: 99%